Developing an English Proficiency Test for Higher Education - Rionaldi, Rionaldi; Saputra, Boni (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
Universities worldwide have recognized the significance of assessing students' language abilities to ensure they can actively participate in academic discourse. However, many universities do not have institution-based English proficiency test yet. The aim of the research is to explore the significances of developing university-based English proficiency test, the essential steps involved in crafting it, and challenges in developing a robust institution's English proficiency test. The method used in this research is library research. The results underscore the critical role of an English proficiency test in ensuring academic excellence, promoting global communication, and preparing students for success in an increasingly interconnected world. Developing a well-structured and reliable English proficiency assessment tool starts with a decision to provide a test, developing the test, and followed by those stages connected with test use. Nevertheless, defining test objective and ensuring test validity, choosing the right format, ensuring fairness and inclusivity, preparing substantial cost and resources, adapting for specific contexts are challenges in developing it. In sum, universities can develop a robust English proficiency test by having collaboration with language experts, assessment specialists, and educators, as well as adherence to established principles of language testing and assessment .